Lessons from Genetic Studies of Primary Immunodeficiencies in a Highly Consanguineous Population - Barbouche, Mohamed-Ridha; Mekki, Najla; Ben-Ali, Meriem; Ben-Mustapha, Imen (Frontiers in Immunology, 2017)
During the last decades, the study of primary immunodeficiencies (PIDs) has contributed tremendously to unravel novel pathways involved in a variety of immune responses. Many of these PIDs have an autosomal recessive (AR) mode of inheritance. Thus, the investigation of the molecular basis of PIDs is particularly relevant in consanguineous populations from Middle East and North Africa (MENA). Although significant efforts have been made in recent years to develop genetic testing across the MENA region, few comprehensive studies reporting molecular basis of PIDs in these settings are available. Herein, we review genetic characteristics of PIDs identified in 168 patients from an inbred Tunisian population. A spectrum of 25 genes involved was analyzed. We show that AR forms compared to X-linked or autosomal dominant forms are clearly the most frequent. Furthermore, the study of informative consanguineous families did allow the identification of a novel hyper IgE syndrome linked to PGM3 mutations. We did also report a novel form of autoimmune lymphoproliferative syndrome caused by homozygous FAS mutations with normal or residual protein expression as well as a novel AR TCF3 deficiency. Finally, we identified several founder effects for specific AR mutations. This did facilitate the implementation of preventive approaches through genetic counseling in affected consanguineous families. All together, these findings highlight the specific nature of highly consanguineous populations and confirm the importance of unraveling the molecular basis of genetic diseases in this context. Besides providing a better fundamental knowledge of novel pathways, their study is improving diagnosis strategies and appropriate care.